SOCIAL MEDIA-BASED PUBLIC RELATIONS MANAGEMENT IN IMPROVING SCHOOL BRANDING IN MADRASAH ALIYAH - Zaenudin Khabib; Muhammad Khoiruddin; Sukarman Sukarman (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
This study aims to analyze the evolution of research on the digital divide in In this fast-paced digital era, Islamic Senior High Schools (Madrasah Aliyah) now find themselves at a crossroads between preserving traditional values and responding to global innovation. School branding is no longer simply about a logo or slogan, but about building a narrative that touches the hearts and builds public trust. This paper examines a public relations management strategy that utilizes social media not merely as a broadcasting tool but as a bridge for empathetic dialogue. Through authentic content planning, warm interactions, and visual consistency, Islamic senior high schools can transform their image into a modern, competitive institution, while remaining rooted in their religious identity. The analysis shows that public relations management with a humanistic approach on social media effectively strengthens public loyalty and reinforces the school's branding position amidst the dynamic competition in education.